PENGARUH PENDAPATAN DAN BIAYA OPERASIONAL TERHADAP BEBAN PAJAK PADA PT JEMBO CABLE COMPANY TBK - Nela Dharmayanti (FEB Universitas Sultan Ageng Tirtayasa, 2018)
This study aims to determine the effect of income and operational costs on the tax burden on PT Jembo Cable Company Tbk. This study uses secondary data taken from the financial statements of PT Jembo Cable Company Tbk through the IDX website. The population used in all financial statements. The number of samples taken by 30 samples of financial statements on a quarterly basis in the period 2016 - 2010. The method used in this method is the descriptive method. The testing was carried out using the help of SPSS Software 24.00. The results of research and discussion t test shows income (X1) to the tax burden (Y) shows that income has a significant effect on tax expense while the t test of operational costs (X2) on tax expense (Y) shows that operating costs have a significant effect on tax expense. F test between income (X1) and operating costs (X2) on tax expense (Y), the positive and significant effect between income and operating costs on tax expense. The implications of the above conclusions, namely income and operating costs have a positive influence on the tax burden to reduce the tax burden, so companies must do tax planning efforts to reduce tax burden.